Role of Motivation in Academic Achievement among Medical Students: Mediating Role of Self-Efficacy : Role of Motivation in Academic Achievement - Habib, Atiqa; Hanif, Rabia; Riaz, Rabia (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Motivation acts as a major factor in making sound decisions and actions. The following study was conducted to investigate the relationship between motivation and academic achievement among medical students, along with exploring the mediating role of self-efficacy. Objective: To look for the relationship within motivation, academic achievement and self-efficacy among medical students, investigate the mediating role of self-efficacy among motivation and academic achievement and to investigate the role of various demographic factors. Methods: To test the hypothesis, questionnaires used for accessing motivation and academic achievement were SMMS-R and percentages whereas self-efficacy was measured via General Self-efficacy and Academic Self-efficacy scale. The study sample includes females (n=183) and males (n=115) with MBBS student being the inclusion criteria and non-MBBS students set as exclusion criteria where the data were collected through convenience sampling technique and calculated based on G-power. Results: were analyzed through Statistical Package for Social Sciences (SPSS) version 26.0 using Pearson Correlation to see the relationship between variables and independent sample t-test to see gender differences. Results showed Academic achievement was positively correlated with the motivation. A significant positive correlation of motivation with General self-efficacy and a strong negative correlation was found between Academic Self-efficacy and strength of motivation among medical students. Conclusions: By using this study, we will be able to understand the role of motivation and self-efficacy on academic achievement among medical students and how it varies across gender.